2013
DOI: 10.1007/s12034-013-0546-0
|View full text |Cite
|
Sign up to set email alerts
|

Study on photocatalysis of TiO 2 nanotubes prepared by methanol-thermal synthesis at low temperature

Abstract: TiO 2 nanotubes were synthesized by the solvothermal process at low temperature in a highly alkaline water-methanol mixed solution. Their characteristics were identified by powder X-ray diffraction (XRD), transmission electron microscopy (TEM), specific surface area (BET), Fourier transform infrared spectroscopy (FTIR) and UV-Vis absorption spectroscopy. The as-prepared samples were tested by the photodegradation reaction of methylene blue (MB) dye under visible-light irradiation. The ratios of methanol and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 30 publications
(34 reference statements)
1
15
0
1
Order By: Relevance
“…However, it can be observed that calcination slightly increased the photocatalytic activity of titanate nanotubes. Nam et al (2013) also reported slightly faster degradation of methylene blue in the presence of calcined titania nanotubes and attribute this increase of degradation rate to the appearance of low amount of anatase phase. We believe that increased photocatalytic activity of calcined nanotubes is a consequence of both, the presence of anatase, i.e.…”
Section: Resultsmentioning
confidence: 86%
“…However, it can be observed that calcination slightly increased the photocatalytic activity of titanate nanotubes. Nam et al (2013) also reported slightly faster degradation of methylene blue in the presence of calcined titania nanotubes and attribute this increase of degradation rate to the appearance of low amount of anatase phase. We believe that increased photocatalytic activity of calcined nanotubes is a consequence of both, the presence of anatase, i.e.…”
Section: Resultsmentioning
confidence: 86%
“…Figure shows X‐ray diffraction patterns of the precursor (a) and the photocatalyst synthesized at 155°C before calcination (b) and after calcination at 700°C (c). In the diffraction pattern of the precursor (a), peaks at 2θ° of 25.42, 37.87, 48.12, and 75.12 are allocated to anatase …”
Section: Resultsmentioning
confidence: 99%
“…The as-spun multi-component 6 nanostructure was stabilized and then carbonized to obtain a well-designed TiO 2 @ZnO carbon non-woven hollow nanofiber by burning PVP and transforming TBOT, ZnCl 2 and PAN to TiO 2 , ZnO and the graphite carbon, respectively. Subsequently, high porous TiO 2 brush-like nanotube arrays attached onto 3D graphite carbon hollow nanofibers obtained by employing the alkaline (10.0 M NaOH) hydrothermal process in a Teflon-lined stainless steel autoclave at 130 °C for 24 h with subsequent acid-washing and annealing treatment at 420 °C ( Figure S1) 31,[44][45] .…”
Section: Resultsmentioning
confidence: 99%